GILL COMMUNITY STRUCTURE AND SPATIAL ALLOCATION OF CICHLIDOGYRID MONOGENEAN PARASITES ON THE GILLS OF Oreochromis niloticus (LINNÉ, 1758) OF YSR DISTRICT, ANDHRA PRADESH, INDIA - VANKARA, ANU PRASANNA; MODI, ASHA KIRAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Background and Objectives: Monogeneans are notorious parasites with a diverse life-history which occupy hydrodynamically secluded sites within the gill arches to defend themselves from strong water currents and pesticides in water. A parasitic survey was performed to emphasize the spatial distribution of gill monogeneans from Oreochromis niloticus (Linné, 1785) of different localities of YSR District, Andhra Pradesh. Materials and Methods: Routine parasitological procedures were employed to screen the gills of the fishes for the monogenean infection and standard statistical softwares (IBM SPSS 21.0 version) were used to conduct statistical tests. Results: A total of 4028 monogeneans of the genus Cichlidogyrus and Scutogyrus were obtained from the gills of 133 examined fishes with a prevalence of 75.9%, mean intensity of 39.8 and mean abundance of 30.2 respectively. All the 3 species of monogeneans, Cichlidogyrus sclerosus, Cichlidogyrus tilapiae and Scutogyrus longicornis were of common occurrence (Prevalence >50%) and showed an aggregated distribution pattern (16.4, 15.3 and 12.3). C. sclerosus was the core species while the remaining were secondary species. The relationship between the condition factor and parasitic abundance showed a significant correlation. Parasitization was highest in winter (47%) and least in summer seasons (22%). Conclusion: Location-wise analyses of parasites, preference for sides of the fish host, influence of host size and host sex on parasitization were analysed. Gill community structure and spatial allocation studies of these parasites help the aquaculturists in the proper health management of the fishes and reduce economic losses.